Contested Constitutional Legitimacy in Indonesian Foreign Policy: Islamic Organizations and the Board of Peace Controversy - Firman Robiansyah; Abigail Latasya Karim; Ceysia Attira Fauzi; Fauzan Rahmat Ramadhan; Mochammad Rashya Danovan; Zahid Abdurrahman Al Haliim (IAIN Bone, 2026)
The Board of Peace controversy reveals a contestation over constitutional legitimacy in Indonesian foreign policy. This article examines how Indonesia’s participation generated competing interpretations of the Preamble to the 1945 Constitution, the “free and active” principle as enshrined in Law No. 37 of 1999 on Foreign Relations, and Article 11 on executive–legislative authority. Using socio-legal research and critical discourse analysis, it analyzes government statements, parliamentary debates, media coverage, and public statements issued by Islamic organizations. The findings show that the government justified participation by invoking the constitutional mandate to contribute to world peace and an “inside-to-steer” strategy, while parliament emphasized oversight and procedural legitimacy. Islamic organizations invoked anti-colonialism, humanitarian solidarity, and support for Palestinian self-determination. The article argues that constitutional interpretation in foreign policy extends beyond formal institutions to include civil society actors with normative authority.